Pharmacy Practice and Therapeutics: Life Sciences-Pharmacy - Sr. K. MARIA SUNDARI, CHIEF PATRON (International Journal of Life Science and Pharma Research, 2020)
International Conference on Therapeutics and Pharmacy Practice - ‘‘Exploring and Advancing Healthcare through Novel Strategies in Pharmacy Practice’’ organized by Nirmala College of Pharmacy, Mangalagiri in collaboration with Findlay University, USA & Pharmacon Society, Hyderabad held on 17th& 18th December, 2019. The Conference main objectives are to cultivate an international forum for the ever widening scope of Pharmacy Practice research, to Create a forum for the dissemination of quality, international Pharmacy Practice research for all stake holders, to increase Pharmacy Practice contributions to global health through the provision of greater access to the latest high quality international Pharmacy Practice and to develop a policy statement on current and future Pharmacy Practice research.